Bioactivation versus detoxication of the urothelial carcinogen aristolochic acid I by human cytochrome P450 1A1 and 1A2 - Stiborová, Marie; Levová, Katerina; Bárta, Frantisek; Shi, Zhanquan; Frei, Eva; Schmeiser, Heinz H; Nebert, Daniel W; Phillips, David H; Arlt, Volker M (Toxicological sciences, 2012)
Exposure to aristolochic acid (AA) is associated with human nephropathy and urothelial cancer. Individual susceptibility to AA-induced disease likely reflects individual differences in enzymes that metabolize AA. Herein, we evaluated AAI metabolism by human cytochrome P450 (CYP) 1A1 and 1A2 in two CYP1A-humanized mouse lines that carry functional human CYP1A1 and CYP1A2 genes in the absence of the mouse Cyp1a1/1a2 orthologs. Human and mouse hepatic microsomes and human CYPs were also studied. Human CYP1A1 and 1A2 were found to be principally responsible for reductive activation of AAI to form AAI-DNA adducts and for oxidative detoxication to 8-hydroxyaristolochic acid (AAIa), both in the intact mouse and in microsomes. Overall, AAI-DNA adduct levels were higher in CYP1A-humanized mice relative to wild-type mice, indicating that expression of human CYP1A1 and 1A2 in mice leads to higher AAI bioactivation than in mice containing the mouse CYP1A1 and 1A2 orthologs. Furthermore, an exclusive role of human CYP1A1 and 1A2 in AAI oxidation to AAIa was observed in human liver microsomes under the aerobic (i.e., oxidative) conditions. Because CYP1A2 levels in human liver are at least 100-fold greater than those of CYP1A1 and there exists a > 60-fold genetic variation in CYP1A2 levels in human populations, the role of CYP1A2 in AAI metabolism is clinically relevant. The results suggest that, in addition to CYP1A1 and 1A2 expression levels, in vivo oxygen concentration in specific tissues might affect the balance between AAI nitroreduction and demethylation, which in turn would influence tissue-specific toxicity or carcinogenicity.
Keywords: Microsomes, Liver; Dealkylation; Cytochrome P-450 CYP1A2; Recombinant Proteins; adukty DNA; Mice, Knockout; Inactivation, Metabolic; vysokoúčinná kapalinová chromatografie; Cytochrome P-450 CYP1A1; urotel; metabolická inaktivace; Urologic Neoplasms; cytosol; cytochrom P-450 CYP1A1; Enzyme Inhibitors; dealkylace; Aristolochic Acids; Cytochrome P-450 CYP1A2 Inhibitors; inhibitory cytochromu P450 CYP1A2; Cytosol; Chromatography, High Pressure Liquid; myši knockoutované; oxidace-redukce; Urothelium; rekombinantní proteiny; cytochrom P-450 CYP1A2; kyseliny aristolochové; Animals; lidé; ženské pohlaví; játra; myši transgenní; Carcinogens; karcinogeny; Humans; zvířata; DNA Adducts; myši inbrední C57BL; Mice, Transgenic; myši; Mice, Inbred C57BL; Liver; Oxidation-Reduction; Mice; urologické nádory; Female; inhibitory enzymů; jaterní mikrozomy